Genome, and beyond - Yip, Y. L.; Section Editor for the IMIA Yearbook Section on Bioinformatics (Yearbook of Medical Informatics, 2011)
To summarize current excellent research in the field of bioinformatics, with an emphasis on those that have direct application in the medical domain.Synopsis of the articles selected for the IMIA Yearbook 2011.The selection process for this yearbook’s section on Bioinformatics results in six excellent articles highlighting the continuous progress towards a better understanding of human phenotype. Compared to the selection in Yearbook 2010, several key advancements can be noted. First, year 2010 marked the inaugural use of a complete human genome in a clinical context. This proof-of-principle study represents a large step towards personalized medicine. Second, there is a clear trend to understand diseases beyond the genome level, namely to include environmental and epigenetic information. Third, an innovative framework making use of the web to harness participant-driven genotype-phenotype information sets a new scene for conducting research in an era where social media plays an increasingly important role.The current literature showed that all pieces are now present to enable a much more comprehensive understanding of human diseases and traits, beyond the highly focused genetic or genomic studies seen previously.
Keywords: Bioinformatics; epigenetics; environment; human genome; phenotype